EVIDENCES OF VARIABLE RESPONSE TO SPOT BLOTCH IN DIFFERENT WHEAT VARIETIES - S. K. BISWAS; P. K. SAHU; JAVED BAHAR; AMARENDRA KUMAR; SANTOSH KUMAR; CHARUL KANCHAN (The Bioscan, 2015)
Comparative studies on seven wheat varieties viz. K 65, K 9107, K 8027, PBW 343, HUW 234 and PBW 443 against spot blotch pathogen have been revealed that K 9107 variety was comparatively resistant against spot blotch pathogen, showing minimum per cent disease index (PDI) with 33.2 % . Biochemical analysis of this wheat variety with respect to N %, crude protein, soluble protein and total phenol content revealed that the less affected varieties possessed higher level of soluble protein and total phenol content, whereas, susceptible variety had higher level of crude protein and N %. The maximum soluble protein (41.45 mg/g of fresh leaf) was recorded in the variety K 9107, which was followed by K 8027 (39.23 mg/g of fresh leaf). The maximum total phenol content 3.02 mg/gm of fresh leaf at 5 days, 2.88 mg/g of fresh leaf, at 10 days, 2.65 mg/gm of fresh leaf at 15 days, and 2.85 mg/g of fresh leaf at 20 days was found in the resistant variety K 9107 at seedling stage. The highest phenol content with 3.92mg/g of fresh leaf was found in variety K 9107 which was followed by K-65 (3.71mg/ g of fresh leaf) at vegetative stage. The variable amount of crude protein, soluble protein and total phenol content resulted different types of disease response to spot blotch in wheat.